Authors Index - COBEC2012 - 2st Brazilian Congress in Electromyography and Kinesiology and 2st National Meeting of Myotherapy Procedures - Piracicaba Dental School UNICAMP (Universidade Estadual de Campinas, 2015)
Authors Index - COBEC2012